2017
DOI: 10.31142/ijtsrd2368
|View full text |Cite
|
Sign up to set email alerts
|

Review Use of Demolished Concrete in Pavement Construction

Abstract: Recycled aggregates consist of crushed, graded inorganic particles processed from the material that have been used in the constructions and demolition debris. The target of the present thesis work is to determine the strength characteristic of recycled aggregates for the application in concrete pavement construction. The scope of the thesis is to determine and compare the compressive strength, flexural strength and sulphate resistance of concrete by using different percentages of recycled aggregates. The inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Kumar and Rathod, (2018) reviewed several literatures and finally suggested the usage of C&D debris to curb detrimental effect of wastes on environment and enhance soil properties. They also suggested the use of polypropene as an economical material with high strength, longevity and non-biodegradability which in turn could improve soil properties leading to soil stabilization [9]. Bhat and Gupta, (2018) examined and analyzed the various sorts of researches on the use of C&D waste in pavement subgrade.…”
Section: Various Materials Used For Improvement Of Soil Engineeringmentioning
confidence: 99%
“…Kumar and Rathod, (2018) reviewed several literatures and finally suggested the usage of C&D debris to curb detrimental effect of wastes on environment and enhance soil properties. They also suggested the use of polypropene as an economical material with high strength, longevity and non-biodegradability which in turn could improve soil properties leading to soil stabilization [9]. Bhat and Gupta, (2018) examined and analyzed the various sorts of researches on the use of C&D waste in pavement subgrade.…”
Section: Various Materials Used For Improvement Of Soil Engineeringmentioning
confidence: 99%
“…Kumar et al reviewed several literatures and finally suggested the usage of C&D debris to curb detrimental effect of wastes on environment and enhance soil properties. They also suggested the use of polypropene as an economical material with high strength, longevity and non-biodegradability [9]. Bhat et al examined and analyzed the various sorts of researches on the use of C&D debris in pavement subgrade.…”
Section: Literature Reviewmentioning
confidence: 99%